Suicidal ideation and depressive symptoms among bipolar patients as predictors of the health and well-being of caregivers. - Chessick, C; Perlick, D; Miklowitz, D; Dickinson, L; Allen, M; Morris, C; Gonzalez, J; Marangell, L; Cosgrove, V; Ostacher, M (2009)
OBJECTIVES: Few studies have addressed the physical and mental health effects of caring for a family member with bipolar disorder. This study examined whether caregivers' health is associated with changes in suicidal ideation and depressive symptoms among bipolar patients observed over one year. METHODS: Patients (N = 500) participating in the Systematic Treatment Enhancement Program for Bipolar Disorder and their primary caregivers (N = 500, including 188 parental and 182 spousal caregivers) were evaluated for up to one year as part of a naturalistic observational study. Caregivers' perceptions of their own physical health were evaluated using the general health scale from the Medical Outcomes Study 36-item Short-Form Health Survey. Caregivers' depression was evaluated using the Center for Epidemiological Studies of Depression Scale. RESULTS: Caregivers of patients who had increasing suicidal ideation over time reported worsening health over time compared to caregivers of patients whose suicidal ideation decreased or stayed the same. Caregivers of patients who had more suicidal ideation and depressive symptoms reported more depressed mood over a one-year reporting period than caregivers of patients with less suicidal ideation or depression. The pattern of findings was consistent across parent caregivers and spousal caregivers. CONCLUSIONS: Caregivers, rightly concerned about patients becoming suicidal or depressed, may try to care for the patient at the expense of their own health and well-being. Treatments that focus on the health of caregivers must be developed and tested.